Fashion, Feminism, and the Pleasures and Perils of Consumer Fantasy - Jacobson, Lisa (Journal of Women's History, 2010)
Bodies, social rituals, and consumer display are all powerful testing grounds for gender performance. A minor dustup between Hillary Clinton and Vogue editor Anna Wintour during Clinton's 2008 presidential campaign attests to just how high (and preposterous) the political stakes in gender performance can be. Clinton had been scheduled to do a photo shoot for Vogue but backed out at the last minute, to Wintour's dismay, because her advisors feared she might appear "too feminine." Wintour's editor's column in the February 2008 issue upbraided Clinton for her outmoded ways: "Imagine my amazement . . . when I learned that Hillary Clinton . . . had decided to steer clear of our pages . . . for fear of looking too feminine. The notion that a contemporary woman must look mannish in order to be taken seriously as a seeker of power is frankly dismaying." The Wintour–Clinton quarrel seems silly and petty given the larger stakes in the election, but it also cuts to the heart of feminist debates that the authors of several recent books on fashion, beauty culture, weddings, and bridal showers engage. Is feminine style compatible with feminist substance? Are beauty salons, weddings, and fashion sources of women's oppression or might they provide women with avenues for self-expression or even the tools of resistance? Do the politics of style give some feminists more street cred than others? In varying ways, the books reject the austere moralism of early feminists and theorists of consumption who associated style consciousness with false consciousness and frivolous desires. Fashion, beauty culture, and weddings, these books show us, are not trivial matters but rich subjects for historical and sociological analysis that reveal much about the politics of style, the ongoing struggles to limit and expand women's power, and the contested meanings of consumption. Linda Scott's Fresh Lipstick, the most polemical of the bunch, picks up Wintour's cudgel in tracing the history of feminism's antibeauty ideology from Susan B. Anthony to Gloria Steinem. Feminists have long criticized mainstream fashion for constraining women's physical movement, glorifying women as sex objects, and encouraging them to invest more in superficial appearances than their intellectual development. Beneath this seemingly liberatory rhetoric, Scott argues, lay a more sinister campaign by feminists to control other women and demean the feminist credentials of fashionable women. She cites, for example, Anthony's success in blocking the nomination of Elizabeth Oaks Smith, a respected feminist, to serve as president of the 1852 Women's Convention on grounds that Smith's fashionable attire called into question the seriousness of her commitment to equal rights. Instead of encouraging individuality and freedom from convention, the feminist politics of dress, Scott laments, demanded puritanical conformity in appearance. The so-called "natural look" advocated by second-wave feminists—a makeup-free, unshaven body and a gender-neutral ensemble of jeans, T-shirts, and sturdy, heelless shoes—merely substituted one kind of fashion orthodoxy for another. Ms. Magazine, Scott charges, "seemed intent on making every act of vanity a political litmus test" (302). Such reductionist approaches to fashion, Scott argues, blinded feminists to their own contradictions. Feminists decried cosmetics as a violation of the natural aesthetic yet sanctioned tattooing—itself a form of adornment—as an act of gender rebellion. The line between artifice and authenticity, Scott rightly notes, is not so easily drawn. Scott argues that antibeauty ideology unfairly denigrated women's yearnings for pretty clothes and pleasure and denied the legitimacy of other feminisms. Instead of castigating Sarah Josepha Hale for spreading the cult of true womanhood, as many feminists have, Scott casts the editor of the fashion-laden Godey's Ladies' Book as an engaged feminist, citing her support for women's property rights and admission to the professions, and her editorial criticisms of women's rigid adherence to fashion. Instead of ostracizing the career women who wrote cosmetics ads, Scott lauds them for seeking testimonials from women suffragists. Even Clairol's famous "Does she or doesn't she?" hairdye ads from the 1960s—a campaign that seemingly reduces women to sex objects—acquires new meaning on closer inspection. The sexual double entendre seems unmistakable, but the ads actually attempted to desexualize and mainstream...
Keywords: Business History and gender